BTNL2‐Ig Protein Attenuates Type 1 Diabetes in Non‐Obese Diabetic (NOD) Mice. Issue 9 (18th March 2019) - Tian, Xiaohong; Lin, Yujun; Cui, Cheng; Su, Min; Lai, Laijun
Abstract: Type 1 diabetes (T1D) is a T cell‐mediated autoimmune disease in which insulin‐producing β ‐cells are destroyed. Although butyrophilin‐like 2 (BTNL2) has been shown to be a negative T cell regulator in vitro, its ability to inhibit T cell responses in vivo has not been determined. In this study, the effect of a recombinant BTNL2‐IgG2a Fc (rBTNL2‐Ig) fusion protein on T1D development in vivo is determined. It is shown here that in vivo administration of rBTNL2‐Ig ameliorates T1D in non‐obese diabetic (NOD) mice. This is associated with the ability of rBTNL2‐Ig to inhibit the proliferation, activation, and inflammatory cytokine production from autoreactive T cells in vivo. In addition, rBTNL2‐Ig treatment increases the generation of regulatory T cells. The results suggest that targeting the BTNL2 pathway has the potential to be used in the prevention and treatment of patients with T1D. Abstract : Recombinant butyrophilin‐like 2 (BTNL2)‐IgG2a Fc (rBTNL2‐Ig) fusion protein is examined for its effect on Type 1 diabetes (T1D), a T cell‐mediated autoimmune disease. rBTNL2‐Ig ameliorates T1D in non‐obese diabetic (NOD) mice, which correlates with its ability to inhibit T cell function; consequently, rBTNL2‐Ig may provide a useful treatment of T1D patients.